2016
DOI: 10.1103/physreve.94.012619
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a model colloidal suspension from dilute to freezing

Abstract: Molecular dynamics simulation was used to study a model colloidal suspension at a range of packing fractions from the dilute limit up to the freezing point. This study builds on previous work by the authors which modeled the colloidal particles with a hard core surrounded by a Weeks-Chandler-Anderson potential with modified interaction parameters, and included an explicit solvent. In this work, we study dynamical properties of the model by first calculating the velocity autocorrelation function, the self-diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 58 publications
7
13
1
Order By: Relevance
“…We found that at finite wavevectors the intermediate scattering function could be modelled as a double exponential decay with e↵ective short-and long-time di↵usion coe cients [13]. This is in line with experimental analysis [17], though our definition of the short-time di↵usion coe cient di↵ers from the usual convention.…”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…We found that at finite wavevectors the intermediate scattering function could be modelled as a double exponential decay with e↵ective short-and long-time di↵usion coe cients [13]. This is in line with experimental analysis [17], though our definition of the short-time di↵usion coe cient di↵ers from the usual convention.…”
Section: Introductionsupporting
confidence: 85%
“…The explicit solvent was included in the model in an attempt to match the dynamics of a real colloidal suspension by having the larger particles di↵use through a solvent with a viscosity and inertia, rather than moving ballistically through a vacuum. However our attempt to include hydrodynamic interactions was only partially successful as the trend in the self di↵usion coe cients with packing fraction is qualitatively similar to that observed in Brownian dynamics simulations [13]. We calculated the intermediate scattering function (which is a key quantity measured in dynamic light scattering experiments [7,8,11,[14][15][16]) over a large range of packing fractions and wavevectors in order to systematically study the change in dynamics on the approach to the freezing point.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations